2003
DOI: 10.1089/10430340360535788
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose Escalation Clinical Trial of Adenovirus Vector Carrying Osteocalcin Promoter-Driven Herpes Simplex Virus Thymidine Kinase in Localized and Metastatic Hormone-Refractory Prostate Cancer

Abstract: Osteocalcin (OC), a major noncollagenous bone matrix protein, is expressed prevalently in prostate cancer epithelial cells, adjacent fibromuscular stromal cells, and osteoblasts in locally recurrent prostate cancer and prostate cancer bone metastasis [Matsubara, S., Wada, Y., Gardner, T.A., Egawa, M., Park, M.S., Hsieh, C.L., Zhau, H.E., Kao, C., Kamidono, S., Gillenwater, J.Y., and Chung, L.W. (2001). Cancer Res. 61, 6012-6019]. We constructed an adenovirus vector carrying osteocalcin promoter-driven herpes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 28 publications
1
70
0
1
Order By: Relevance
“…44,45 The safety of an adenoviral vector carrying OC promoter-driven HSV-TK gene was also recently demonstrated in a Phase I clinical trial. 46 The major side effect of high-dose vitamin D administration is hypercalcemia, which would jeopardize its clinical utility. Although the vitamin D 3 analogue Ro 25-9022, used in the present study, has not been tested at the maximum tolerated dose, when mice treated with 4 ng of Ro 25-9022 twice per week were compared with untreated mice, they showed only a mild side effect, a less than 10% body weight reduction for a period of 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 The safety of an adenoviral vector carrying OC promoter-driven HSV-TK gene was also recently demonstrated in a Phase I clinical trial. 46 The major side effect of high-dose vitamin D administration is hypercalcemia, which would jeopardize its clinical utility. Although the vitamin D 3 analogue Ro 25-9022, used in the present study, has not been tested at the maximum tolerated dose, when mice treated with 4 ng of Ro 25-9022 twice per week were compared with untreated mice, they showed only a mild side effect, a less than 10% body weight reduction for a period of 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy has been of limited value because most patients do not respond to secondary manipulations after developing hormone-refractory disease (3). Significant advances have been made in gene therapy, and several clinical trials have been in progress over recent years as a result of developments in molecular and cell biology (4)(5)(6)(7)(8)(9)(10). Thus, it is important to develop novel therapeutic approaches and to explore the use of gene therapy as an alternative treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…In this trial, an adenovirus vector carrying osteocalcin promoter-driven HSVtk was used to target both prostate cancer cells and their neighboring stromal cells and valacyclovir, another anti herpetic prodrug converted to aciclovir, was given orally. The results showed a good tolerance with no serious adverse events but with local cell death in treated lesions in 63.6% of patients (Kubo et al 2003). In another clinical phase I/II study, 36 prostate cancer patients with local recurrence after radiotherapy which received single or repeated cycles of adenoviral vector-mediated HSVtk/GCV intraprostatic gene therapy (Miles et al 2001) showed no significant side effects and a significant increase in biological responses such as the mean serum PSA-doubling time (PSADT), prostate-specific antigen recurrence (PSAR), return to initial PSA (TR-PSA), and activated CD8(+) T cells present in the peripheral blood.…”
Section: Clinical Trialsmentioning
confidence: 84%